Mechanical properties of irradiated nanowires - A molecular dynamics study - Figueroa, Emilio (2015)
In this work we study, by means of molecular dynamics simulation, the change in the mechanical properties of a gold nanowire with pre-existing radiation damage. The gold nanowire is used as a simple model for a nanofoam, made of connected nanowires. Radiation damage by keV ions leads to the formation of a stacking fault tetrahedron (SFT), and this defect leads to a reduced plastic threshold, as expected, when the nanowire is subjected to tension. We quantify dislocation and twin density during the deformation, and find that the early activation of the SFT as a dislocation source leads to reduced dislocation densities compared to the case without radiation damage. In addition, we observed a total destruction of the SFT, as opposed to a recent simulation study where it was postulated that SFTs might act as self-generating dislocation sources. The flow stress at large deformation is also found to be slightly larger for the irradiated case, in agreement with recent experiments.